2021
DOI: 10.1007/s00127-021-02093-x
|View full text |Cite
|
Sign up to set email alerts
|

Multi-trajectory group profiles of well-being and associated predictors among adults experiencing homelessness and mental illness: findings from the At Home/Chez Soi study, Toronto site

Abstract: Purpose To conduct a multi-dimensional and time-patterned analysis to identify distinct well-being trajectory profiles over a 6-year follow-up period among adults experiencing homelessness and mental illness. Methods Data from 543 participants of the At Home Chez Soi study’s Toronto site were examined over a 6-year follow-up period, including measures of quality of life, community functioning, housing stability, and substance use. Well-being trajectories w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Spatial analyses of crime and disorder were conducted in the immediate vicinity of OPCs and comparison sites and, to assess possible spillover effects, in the wider neighborhoods surrounding these sites. Following the methods of prior studies with a similar objective, 27 , 28 , 29 we divided the city into discrete areas by overlaying a block-level map of NYC with a tessellated hexagonal array, centering the hexagons to demarcate areas around OPCs and comparison sites. Hexagons were used because they can be tessellated without geographic omission or the need for alteration and have the least internal variation in their radii.…”
Section: Methodsmentioning
confidence: 99%
“…Spatial analyses of crime and disorder were conducted in the immediate vicinity of OPCs and comparison sites and, to assess possible spillover effects, in the wider neighborhoods surrounding these sites. Following the methods of prior studies with a similar objective, 27 , 28 , 29 we divided the city into discrete areas by overlaying a block-level map of NYC with a tessellated hexagonal array, centering the hexagons to demarcate areas around OPCs and comparison sites. Hexagons were used because they can be tessellated without geographic omission or the need for alteration and have the least internal variation in their radii.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous systematic review of social interventions for people with SMI ( 10 ) suggested that the supported accommodation MoC can support consumers' social inclusion. This review also provided some evidence that it could improve personal recovery outcomes such as hope and subjective wellbeing ( 74 , 79 ). The studies in the goal-focused and the social and community connection-focused MoCs reported encouraging improvement in some functional and personal recovery outcomes, but we found only limited evidence for the vocational support MoC in improving clinical, personal, or functional recovery ( 80 , 83 , 86 , 87 ).…”
Section: Narrative Synthesismentioning
confidence: 99%
“…An umbrella review of the literature on the prevalence of mental health disorders among PEH found a high prevalence of depressive disorders, substance use disorders, stress disorders, and bipolar and mood disorders among adults who were homeless (Hossain et al, 2020). In a study of the association between mental health disorders and well-being, a higher number of mental comorbidities, a higher severity of mental health symptoms, or having alcohol and substance use disorders, were associated with lower well-being profiles (Mejia-Lancheros et al, 2021). Homelessness, early life poverty, mental illness, and substance use were linked with a lower physical and emotional health status and decreased well-being (Fazel et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%